China Satellite Navigation Conference (CSNC) 2013 Proceedings c - Sun, Jiadong; Jiao, Wenhai; Wu, Haitao; Shi, Chuang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
China Satellite Navigation Conference (CSNC) 2013 Proceedings presents selected research papers from CSNC2013, held on 15-17 May in Wuhan, China. The theme of CSNC2013 is: BeiDou Application: Opportunities and Challenges. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou system especially. They are divided into 9 topics to match the corresponding sessions in CSNC2013, which broadly covered key topics in GNSS. Readers can learn about the BeiDou system and keep abreast of the latest advances in GNSS techniques and applications. SUN Jiadong is the Chief Designer of the Compass/BeiDou system, and the Academician of Chinese Academy of Sciences (CAS); JIAO Wenhai is a researcher at China Satellite Navigation Office; WU Haitao is a professor at Navigation Headquarters, CAS; SHI Chuang is a professor at Wuhan University.
BeiDou/GNSS Navigation Applications -- Satellite Navigation Signal System, Compatibility & Interoperability -- Precise Orbit Determination and Positioning -- Atomic Clock Technique and Time-Frequency System -- Satellite Navigation Augmentation and Integrity Monitoring -- BeiDou/GNSS Test and Evaluation Technology -- BeiDou/GNSS User Terminal Technology -- Satellite Navigation Models and Methods -- Integrated Navigation and New Methods.
Keywords: Engineering; Physical geography; Geographical information systems; Astronautics; Telecommunication; Engineering; Aerospace Technology and Astronautics; Communications Engineering, Networks; Geographical Information Systems/Cartography.; Geophysics/Geodesy.